Protocol to measure monosynaptic connections between different cortical regions in mice using cell-pair cross correlogram of spike events - Cong Wang; Montana Samantzis; Matilde Balbi (STAR Protocols, 2024)
Summary: Neuromodulation can facilitate interactions between neurons to rescue impaired brain function after stroke. Here, we present a protocol for measuring putative monosynaptic connections between different cortical regions. We detail procedures for tetrode fabrication, implantation surgery, stroke induction in mice, multi-site in vivo electrophysiological recording, units clustering, principal neuron/interneuron classification, and functional connection analysis. This protocol allows us to understand the mechanisms of stroke recovery.For complete details on the use and execution of this protocol, please refer to Wang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.